The adoption of social media in a South African banking organisation :a qualitative diffusion of innovation perspective - Mehlomakulu, Sidima (My University, 2019)
Social media adoption has seen a rise across businesses in recent history, this is also seen in the increase of publications related to this subject. ICT adoption studies have used many theoretical lenses, in multiple contexts to observe the diffusion phenomenon at an organisational level. However, the understanding of the adoption of social media in large South African organisations has scant research. This study explores the antecedents surrounding the decision to adopt social media, in a South African banking organisation, using an extended Diffusion of Innovation (DOI) theoretical framework. Qualitative, semi-structured interviews are deployed as the methods used to gather insights from decision makers and other impacted business functional areas, to gain a richer understanding of the phenomena. The theoretical contribution of this study provides an enriched understanding of social media diffusion in a South African banking organisational setting, by incorporating concepts of strategy, vision and goals, internal organisational social and cultural structures, as well as external and competitive pressures to the DOI theory. Findings suggest that further concepts such as reputational risk, social media innovativeness and organisational change, could be further explored. Practically, the findings may be used in the decision process of social media implementation, social media strategy development and to improve business operational efficiencies.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Commerce in Information Systems, 2019
Keywords: Banks and banking, Mobile--South Africa; Customer relations--South Africa; Social media--South Africa